Implementing Indonesia’s marriage-age reform: Child marriage dispensation and girls’ health rights - Khofifah Indah Imas Syuroya; Nilna Husnayain (Al'Adalah, 2025)
In Indonesia, marriage age reform has been implemented by raising the minimum age limit to 19 years as an effort to prevent child marriage. However, in practice, this reform faces dispensations that were initially designed as emergency exceptions but have instead become the primary mechanism of implementation, normalising exceptions and shifting the logic of protection to procedural compliance. This article analyses the transformation of these dispensations and their implications for girls' reproductive health rights at the grassroots level. Using a qualitative juridical-empirical approach with a case study in Nyawangan Village, Tulungagung, data were collected through interviews with KUA officers, health workers, and village officials, as well as observations and document reviews. Framed by the Effectiveness of Law theory, the article reveals that dispensations operate as the practical face of reform through routine administrative processes, driven by social, economic, and institutional pressures, with minimal substantive intervention. As a result, considerations of reproductive health and the psychosocial readiness of girls are often overlooked, creating a gap between procedural legality and substantive protection. This article recommends reinstating dispensations as high-threshold exceptions, subject to strict evidentiary standards, standardised health assessments, and cross-institutional coordination focused on delaying marriage. The implication is that marriage-age reform must be firmly embedded at the normative level and supported by governance that truly centres on the best interests of girls.